PENGARUH SERVICE PERFORMANCE DAN RELATIONSHIP MARKETING TERHADAP LOYALITAS KONSUMEN DENGAN EXPERIENTAL MARKETING SEBAGAI VARIABEL MODERASI - Luhgiatno .; Endang Kurniawati (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2016)
This research is motivated by the market competition in the retail business, which grew very rapidly minimarket. This study aims to determine the effect of service performance and relationship marketing on customer loyalty where experiential marketing as a variable that strengthen loyalty konsumen.Secara particular, the study aims to provide a solution to increase the number of consumers amid increasingly fierce competition minimarket.The variables in this study consisted of four variables: service performance and relationship marketing becomes the independent variable while loyalty becomes the dependent variable. Then experiential marketing as a moderating variable. Research data collection techniques by spreading the questionnaire on consumer minimarket in city Semarang systematically arranged with multiple choice answers are easy to understand. The distribution of questionnaires carried out in the period from April to July 2016 with a sample of some 130 people. Then the data collected through a questionnaire to test the validity and reliability. Hypothesis testing using multiple regression analysis. To obtain regression results BLUES (best linear Unbiased estimated), previously performed classical assumption. Testing the level of moderation in moderation regression analysis (Moderated Regression Analisys/MRA).The results showed that the service performance affect positively and significantly related to loyalty, relationship marketing influence positively and significantly related to loyalty, service performance affects the stronger the loyalty when driven by experiential marketing, relationship marketing effect is getting stronger loyalty when driven by experiential marketing